Lubitsch musicals [videorecording (DVD)]. - Chevalier, Maurice, 1888-1972; Colbert, Claudette; Ruggles, Charlie, 1886-1970; Hopkins, Miriam, 1902-1972; MacDonald, Jeanette, 1903-1965; Lubitsch, Ernst, 1892-1947 (Eclipse (Criterion Collection (Firm)). Lubitsch musicals., 2007)
Love parade: In mythical Sylvania, Queen Louise's cabinet are worried that she will become an old maid, and are delighted when she marries the rougish Count Renard. Unfortunately, he finds his position as Queen's Consort unsatisfying and without purpose, and the marriage soon runs into difficulties. The Love parade introduced the screen operetta genre.